Academics' perspectives of international students in UK higher education. Issue 3 (15th March 2020) - Jabbar, Abdul; Teviotdale, Wilma; Mirza, Mohammed; Mswaka, Walter
ABSTRACT: UK Higher Education (HE) is going through a process of unprecedented change, where large numbers of its student body now come from internationally diverse contexts. These students come from different cultures, backgrounds and educational systems which influence the way they interact, learn and engage with UK HE. Key participants in this engagement and interaction are UK HE academics, who play a significant role in the development of the international student teaching and learning experience. This paper aims to investigate this role and investigate the academic expectations and perceptions of 22 academic tutors across 3 UK HE Business Schools. Within this context the paper will explore how academic knowledge and understanding of international students influence their pedagogical approaches; the participants in the research each had a minimum of three years' teaching experience. Data were analysed using template analysis through the lens of an interpretive approach. The findings indicate that more needs to be done to support the integration of international students in UK HE.